The Effect of Salt on Self-Assembled Actin-Lysozyme Complexes - Guáqueta, Camilo (Biophysical Society, 2006)
We present a combined experimental and computational study of the bundling of F-actin filaments induced by lysozyme proteins. Synchrotron small-angle x-ray scattering results show that these bundles consist of close-packed columnar complexes in which the actin is held together by incommensurate, one-dimensional arrays of lysozyme macroions. Molecular dynamics simulations of a coarse-grained model confirm the arrangement of the lysozyme and the stability of this structure. In addition, we find that these complexes remain stable even in the presence of significant concentrations of monovalent salt. The simulations show that this arises from partitioning of the salt between the aqueous and the condensed phases. The osmotic pressure resulting from the excess concentration of the salt in the aqueous phase balances the osmotic pressure increase in the bundle. These results are relevant for a variety of biological and biomedical problems in which electrostatic complexation between anionic polyelectrolytes and cationic globular proteins takes place, such as the pathological self-assembly of endogenous antibiotic polypeptides and inflammatory polymers in cystic fibrosis.